Role of Arvindasava on Malnutrition in Children: An Ayurveda Insight - Khatri, Anand; Dutt Sharma, Brahm; Kumar Nagar, Rakesh; Ojha, Nisha; Sharma, Sanjeev (International Research Journal of Ayurveda & Yoga, 2025)
Malnutrition in children is a significant global health issue, leading to impaired physical and mental development, weakened immune system. Progressively reducing appetite, encouraging catabolism, increasing demand for nutrients, and repeated cases of morbidity exacerbate malnutrition. A healthy diet or good nutrition is the main factor in children’s growth and development. Addressing malnutrition requires a comprehensive approach that includes dietary interventions, nutrient absorption, and underlying health conditions. In this context, Arvindasava, a traditional Ayurvedic formulation, has gained recognition for its potential in improving the nutritional status of children. Agni is considered the life of living being. To digest food properly, the quality of Agni is crucial. The role of the Agni is superior to that of the food quality because if food is not properly digested, it cannot be used by the body, regardless of how much nutritional content in it. This stunts children’s regular growth and development. Impairment of Agni hampers the digestion and absorption of food which leads to malnutrition in children. The present study reveals that the formulation’s active ingredients such as Arvinda, Amalaki, Haritaki, Musta, and Ushira work synergistically to address multiple facets of malnutrition by improving Pachana (digestion and absorption), Deepana (stimulating appetite) and providing vital nutrients, beneficial as Bruhaniya (Anabolic), balancing the Doshas which helps in Ayusya (life prolonging), preventing Balakshaya (boosting immunity), in malnourished children. Arvindasava plays a crucial role in tackling both the causes and effects of malnutrition in children.